A petrographic and geochemical study of mafic sills within the Transvaal Supergroup, east of the Bushveld Igneous Complex - Netshidzivhe, Thendo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.